2019
DOI: 10.1001/jamaneurol.2019.0534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness Yoga vs Stretching and Resistance Training Exercises on Anxiety and Depression for People With Parkinson Disease

Abstract: IMPORTANCE Clinical practice guidelines support exercise for patients with Parkinson disease (PD), but to our knowledge, no randomized clinical trials have tested whether yoga is superior to conventional physical exercises for stress and symptom management.OBJECTIVE To compare the effects of a mindfulness yoga program vs stretching and resistance training exercise (SRTE) on psychological distress, physical health, spiritual well-being, and health-related quality of life (HRQOL) in patients with mild-to-moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
217
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(243 citation statements)
references
References 53 publications
18
217
2
6
Order By: Relevance
“…Whilst there have been few, if any, pharmacological randomized controlled trials with anxiety as the primary outcome in PD, there has been a small number of non-pharmacological studies. A recent study demonstrated that a weekly mindfulness yoga intervention that lasted 8 weeks reduced anxiety in PD (measured by the Hospital Anxiety and Depression Scale), whereas a weekly stretching and resistance exercise intervention did not [62]. Similar to our study, the reduction in anxiety was both statistically and clinically significant.…”
Section: Plos Onesupporting
confidence: 88%
“…Whilst there have been few, if any, pharmacological randomized controlled trials with anxiety as the primary outcome in PD, there has been a small number of non-pharmacological studies. A recent study demonstrated that a weekly mindfulness yoga intervention that lasted 8 weeks reduced anxiety in PD (measured by the Hospital Anxiety and Depression Scale), whereas a weekly stretching and resistance exercise intervention did not [62]. Similar to our study, the reduction in anxiety was both statistically and clinically significant.…”
Section: Plos Onesupporting
confidence: 88%
“…The improvements in the yoga group were moderate to large. However both groups in the study showed similar signi icant improvement in motor symptoms and mobility [11]. Several other studies also found yoga as a feasible and acceptable complementary therapy in improving motor function in PD [17,18,24].…”
Section: Introductionsupporting
confidence: 61%
“…It is also good to mention the availability of specific treatments that can reduce stress, such as mindfulness-based interventions. Several recent studies have shown that mindfulness can reduce depression and anxiety, and even improve motor symptoms [17]. These courses are usually given in groups of patients, but they may also be offered through online platforms.…”
mentioning
confidence: 99%